Targeted Muscle Reinnervation: Outcomes in Treating Chronic Pain Secondary to Extremity Amputation and Phantom Limb Syndrome - McNamara, Colin T.; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2020)
Background Secondary to vascular disease, oncological resection, or devastating trauma, lower extremity amputations are performed globally at a yearly rate exceeding 1 million patients. Three-quarters of these patients will develop chronic pain or phantom pain, which presents a functional limitation for prosthetic use and contributes to deconditioning and increased mortality. Targeted muscle reinnervation (TMR) presents a surgical solution to this problem as either a primary or secondary intervention.Methods A review of the existing literature was conducted using a combination of the terms “phantom pain” “chronic pain,” “neuroma,” and “targeted muscle reinnervation” in Medline and PubMed.Results Five articles were found which addressed TMR for pain syndromes, four of which involved lower extremity amputation. Four of the articles were retrospective reviews, and one was a randomized control trial. A total of 149 patients were included, of which 82 underwent lower extremity amputation. Ninety-two of the patients underwent prophylactic TMR, of which 57 were secondary procedures.In patients who underwent TMR at the time of amputation, all studies reported a minimal development of symptomatic neuromas (27%). For secondary TMR, near-complete resolution of previous pain was found (90%). Phantom pain was noted to be similar to other studies in the literature but noted to improve over time with both primary (average drop of 3.5 out of 10 points on the numerical rating scale) and secondary (diminishing from 72% of patients to 13% over 6 months) operations.Conclusion Although much of the current literature is limited to retrospective studies with few patients, these data point toward near-complete resolution of neuroma pain after treatment as well as complete prevention of chronic pain if TMR is used as a prophylactic measure during the index amputation.This study was a level of evidence IV.
Keywords: nerve; targeted muscle reinnervation; lower extremity